Rekonstruksi Realitas dan Benturan Budaya pada Narasi Film Komang : Analisis Naratif Tzvetan Todorov - Sopandi Wijaya; A Yuda Triantanto; Akhmad Syafrudin Syahri (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The reconstruction of reality in films has a significant connection to everyday life, particularly in depicting cultural clashes that occur in the context of romantic relationships. Interactions between individuals from different cultural and religious backgrounds are becoming increasingly common, often giving rise to challenges and conflicts in relationship dynamics. Therefore, it is important to understand how films can reflect and interpret these issues. This study aims to identify the reconstruction of reality and cultural clashes present in the narrative of the film “Komang.” The method applied in this study is narrative analysis with a descriptive qualitative approach, which produces descriptive data in the form of written or spoken words from the subjects being studied. The theoretical review used in this study is narrative analysis as proposed by Tzvetan Todorov, which emphasizes the existence of plot structure in a story. The results of this study show that this film depicts the complex and challenging dynamics faced by couples from different cultural and religious backgrounds. In addition, this film also raises crucial social issues, such as cultural and religious differences, as well as the importance of communication in maintaining romantic relationships.